Bertholletia excelsa SEEDS IN THE CERRADO-AMAZON TRANSITION REGION: MORPHOMETRY, COLORIMETRY, VIABILITY AND GERMINATION (Nativa, 2024)
ABSTRACT: The objective of this study was to describe morphometric characteristics of fruits and seeds and evaluate the viability and germination of seeds of Bertholletia excelsa stored on litterfall and under similar microenvironmental conditions to those found in their natural habitat, in a Cerrado-Amazon transition area, Brazil. The morphometric characterization consisted of measurements of diameters and latitudinal and longitudinal circumferences of fruits, exocarp and mesocarp thickness, fruit and seed weights per fruit, number of seeds per fruit, and seed thickness, width, and length. Seed moisture content was determined by the ratio between the fresh and dry weights. Colorimetric characterization was performed for mesocarp, outer and inner seed coats, and internal part of the seeds. Seed viability was evaluated using the tetrazolium test and germination was evaluated using intact seeds without seed coat. Morphometric variability was found for fruits and seeds of B. excelsa, regardless of the air humidity. Fruit color and seed outer coat color changed as the relative air humidity decreased. Variations in relative air humidity during the storage period resulted in a significant decrease (45.31%) in seed moisture content and compromised of the seed physiological quality, decreasing seed viability and germination capacity. B. excelsa seeds are sensitive to variations in air humidity. Storing seeds inside the fruit on litterfall and under similar microenvironmental conditions to their natural habitat for up to 96 days under mean relative air humidity above 65% ensures the maintenance of seed moisture above the critical level (30%). Viable seeds with germination potential present moisture contents above 45%.Keywords: Amazon Rainforest; forest residues; recalcitrance; Brazil nut conservation; extractivism. Sementes de Bertholletia excelsa na transição Cerrado-Amazônia: morfometria, colorimetria, viabilidade e germinação RESUMO: Este estudo objetivou descrever as características morfométricas dos frutos e sementes, e, avaliar a viabilidade e germinação das sementes da B. excelsa armazenadas sob a serapilheira em condições microambientais do seu habitat natural na transição Cerrado-Amazônia brasileira. A caracterização morfométrica incluiu medidas de diâmetros e circunferências latitudinal e longitudinal dos frutos; espessura do exocarpo e do mesocarpo, massa dos frutos e das sementes por fruto, número de sementes por fruto, espessura, largura e comprimento das sementes. A umidade das sementes foi obtida pela razão entre massas. A caracterização colorimétrica ocorreu no mesocarpo, tegumento externo e interno e na parte interna da semente. A viabilidade das sementes foi avaliada pelo teste de tetrazólio e a germinação com sementes destegumentadas e intactas. Observou-se variabilidade morfométrica dos frutos e sementes da B. excelsa independentemente da umidade. A cor do fruto e do tegumento externo da semente mudaram de tonalidade com a redução da umidade relativa do ar. As variações da umidade relativa do ar durante o período de armazenamento influenciaram na redução expressiva de 45,31 % no teor de água das sementes e comprometeu a qualidade fisiológica, diminuindo a viabilidade e capacidade de germinação das sementes. As sementes da B. excelsa são sensíveis as variações de umidade. O armazenamento das sementes dentro do fruto sob a serapilheira em condições microambientais do seu habitat natural por até 96 dias com umidade relativa do ar média acima de 65 %, garante a manutenção da umidade das sementes acima da umidade crítica de 30 %. Sementes viáveis e com poder germinativo apresentam teor de água acima de 45 %.Palavras-chave: Floresta Amazônica; resíduos florestais; recalcitrância; conservação da castanha do Brasil; extrativismo.